Quantifying household wastewater pollutants in Kuching - Ling, Teck Yee; Lee, Nyanti; Siew, Tuck-Fatt (Malaysian Chemical Congress 2002, 2002)
Household wastewater in Kuching is typically channeled into watercourses. Not much is known about the contribution of household wastewater from Kuching City towards water quality degradation. In this study, key pollutants concentrations and loadings were investigated over a two months period of dry season at two housing areas. Results indicated that mean water consumption and wastewater flow were 222.1 l/c/d and 82.5 l/c/d respectively. Dissolved oxygen concentration ranged from 1.38 to 4.22 mg/l. Mean pollutant loadings of BOD5, phosphate, and nitrate were found to be 1,825 mg/c/d, 519 mg/c/d, and 3.3 mg/c/d respectively. With the population of 35,750 from the two housing areas, it is estimated that the mean daily contribution of BOD5, phosphate, and nitrate are 62.9 kg, 18.8 kg and 115 g respectively. Recommendations of control and management of household waste to reduce pollution were proposed.